Secured web application based on CapsuleNet and OWASP in the cloud - Vallabhaneni, Rohith; Somanathan Pillai, Sanjaikanth E. Vadakkethil; Vaddadi, Srinivas A.; Addula, Santosh Reddy; Ananthan, Bhuvanesh (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
The tremendous use of sensitive and consequential information in the advanced web application confronts the security issues. To defend the web application while it processing the information must requires the security system. The detection of attacks of web is made by the payload or HTTP request-based detection in association with the scholars. Some of the scholars provide secured attack model detection; however, it fails to achieve the optimal detection accuracy. In concern with these issues, we propose an innovative technique for the attack detection the web applications. The proposed attack detection is based on the novel deep CapsuleNet based technique and the process begins with pre-processing steps known as decoding, generalization, tokenization/standardization and vectorization. After the pre-processing steps the information are passed to deep CapsuleNet for extracting the features for attaining the temporal dependencies from the sequential data. The subtle patterns in the information also detected using the proposed work. Simulation is effectuated to demonstrate the effectiveness of the proposed work and compared with other existing works. Our proposed system provides better accuracy in detecting the attacks than the state-of-art works.